Effects of Early Hospital-Based Palliative Care Consultation on Length of Stay and Costs of Care at Indonesian Tertiary Hospital - Putranto, Rudi; Shatri, Hamzah; Rajabto, Wulyo; Sumariyono, Sumariyono; Faisal, Edward; Sihwastuti, Sihwastuti (UI Scholars Hub, 2023)
Despite the numerous benefits of palliative care for cancer patients, there have been few studies on palliative care services for terminal cancer patients, particularly near the end of life. This study aimed to evaluate whether there were differences in length of stay and cost of care associated with how early or late a patient received palliative care intervention. Another objective was to compare the length of stay and cost of care of those who received palliative care intervention and those who did not. This study used a cohort retrospective design at Hospital A, Jakarta, Indonesia, from January to December 2019. The diagnosis of terminal cancer was based on medical records. Data on length of stay and costs of care were based on medical records and finance billing. The hospitalized terminal cancer patients (392) were recruited by consecutive sampling. The length of stay and costs of care for patients with advanced cancer who received palliative care consultations were longer and higher than for patients who did not receive them. However, if palliative care consultation is provided early, the increase in length of stay and costs are less.